(untitled) (Proceedings of International Educators Conference, 2024)
A deep bite is a type of malocclusion characterized by a significant vertical overlap of the lower incisors with the upper incisors during jaw closure. A deep bite is one of the most frequently encountered bite anomalies in the daily practice of an orthodontist. According to various data, the prevalence of deep bite among the population varies from 6 to 51%. In the structure of occlusal anomalies, deep bite occupies about 20%. In dentistry, a deep bite is sometimes called a "damaging bite", "reduced bite", "deep incisor or frontal occlusion", "deep incisor occlusion or disocclusion".